STR data from S. Tomé e Príncipe (Gulf of Guinea, West Africa) - Gusmão, Leonor (2001)
Allele frequencies for eight STRs (CD4, FES/FPS, MBPB, TH01, TP53, TPO, F13A1, VWA) were estimated from samples (sized between 279 and 328) of unrelated individuals born in S. Tomé e Príncipe (Gulf of Guinea, West Africa).